Associação entre excesso de peso e sonolência diurna excessiva em trabalhadores em turnos - Santana, Fernanda Vieira Silva (2020)
Introduction: Studies have shown that shift workers are more likely to develop various chronic and metabolic diseases such as overweight and obesity, which one has been associated with excessive daytime sleepiness (EDS) in several studies. Objective: The aim of this study was to investigate the association between nutritional profile and excessive daytime sleepiness. Methods: We invited 258 nursing professionals from the clinical Hospital of the Federal University of Uberlandia; they were classified into three work shifts (day, night, and both shifts). Those professionals were submitted to anthropometric analysis. The Epworth Sleepiness Scale was also performed to classify the EDS of those workers. The Epworth Sleepiness Scale scores equal or greater to 10 were considered as EDS. Results: It was identified excessive daytime sleepiness in 93 (36,04%) of the workers. It was also found that individuals with excessive weight (BMI ≥ 25kg/m²) had a higher odds ratio (OR) for EDS in relation to eutrophic individuals: [OR=2,26; confidence interval (CI): 1,22–4,21; p=0,007]. Conclusion: Excessive weight nursing shift workers are more likely to have EDS. These results demonstrate the necessity for educational intervention programs to promote healthy eating and good sleep quality for these workers.